2004
DOI: 10.1080/15287390490447304
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Study of Human Epithelial Cell Lines Resistant to Killing by Chromium Trioxide

Abstract: CrO3 is cytotoxic for human epithelial 293 kidney cells over a narrow concentration range of approximately 2-8 microM (D50 approximately 3.0 microM); significantly greater toxicity is observed in clonogenic assays (D50 approximately 0.1-1.0 microM). Survival of a small fraction of cells (< or = 0.1%) at CrO3 concentrations between 10(-5) to 10(-3) M, and first-order kinetics of cytotoxicity, rationalized the derivation of a new panel of transformed human epithelial cell lines resistant to cytotoxic concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Such a mechanism has been shown in human epithelial cell lines resistant to killing by CrO 3 [50], and has been observed with other toxic metals such as arsenic, platinum, and antimony [51,52]. The resistance of the B-5Cr cells to both Cr (VI)-and H 2 O 2 -induced cell death would suggest that the mechanism was not a function of alteration of cellular Cr(VI) accumulation.…”
Section: Discussionmentioning
confidence: 91%
“…Such a mechanism has been shown in human epithelial cell lines resistant to killing by CrO 3 [50], and has been observed with other toxic metals such as arsenic, platinum, and antimony [51,52]. The resistance of the B-5Cr cells to both Cr (VI)-and H 2 O 2 -induced cell death would suggest that the mechanism was not a function of alteration of cellular Cr(VI) accumulation.…”
Section: Discussionmentioning
confidence: 91%
“…In vitro models of cellular death-resistance generated via long-term, chronic, and slowly escalating exposure doses are advantageous when studying the role of altered transport and intracellular pharmacodynamics in response to cellular genotoxic stress [37-40]. However, our system is unique in that it models initial molecular events that occur in a normal cell that survived a single, acute, initiating genotoxic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Using human 293 embryonic kidney cells made resistant to Cr(VI) (as assessed by toxicity assays), the authors also showed no difference in cellular morphology between the Cr(VI)-resistant and -sensitive cell lines. These authors reported a significant reduction in Cr(VI) uptake in the resistant cells as measured by the uptake of radiolabeled 51 Cr [128]. The Cr(VI)- resistant cells displayed a greater sensitivity to density-dependent growth inhibition and were found to grow at a slower rate than the wild-type sensitive cells, in the absence of Cr(VI).…”
Section: Chromium Genotoxicity: a Double-edged Swordmentioning
confidence: 99%
“…Moreover, these studies revealed that the observed resistant phenotype was also Cr(VI)-specific, as the Cr(VI)-resistant cells were sensitive to treatment with nickel sulfate. Notably, one draw back of this study of Cr(VI) resistance is that the wild-type cells used to create the resistant subclones, were tumorigenic when injected into nude mice [128]. This implies that these cells may already harbor a genetic predisposition to dysregulation of DNA damage response pathways, leading to Cr(VI) resistance.…”
Section: Chromium Genotoxicity: a Double-edged Swordmentioning
confidence: 99%